False memory for idiomatic expressions in younger and older adults: evidence for indirect activation of figurative meanings - Coane, Jennifer H.; Sánchez-Gutiérrez, Claudia; Stillman, Chelsea M.; Corriveau, Jennifer A. (Frontiers in Psychology, 2014)
Idiomatic expressions can be interpreted literally or figuratively. These two meanings are often processed in parallel or very rapidly, as evidenced by online measures of idiomatic processing. Because in many cases the figurative meaning cannot be derived from the component lexical elements and because of the speed with which this meaning is accessed, it is assumed such meanings are stored in semantic memory. In the present study, we examined how literal equivalents and intact idiomatic expressions are stored in memory and whether episodic memory traces interact or interfere with semantic-level representations and vice versa. To examine age-invariance, younger and older adults studied lists of idioms and literal equivalents. On a recognition test, some studied items were presented in the alternative form (e.g., if the idiom was studied, its literal equivalent was tested). False alarms to these critical items suggested that studying literal equivalents activates the idiom from which they are derived, presumably due to spreading activation in lexical/semantic networks, and results in high rates of errors. Importantly, however, the converse (false alarms to literal equivalents after studying the idiom) were significantly lower, suggesting an advantage in storage for idioms. The results are consistent with idiom processing models that suggest obligatory access to figurative meanings and that this access can also occur indirectly, through literal equivalents.